1988
DOI: 10.3928/1542-8877-19881101-15
|View full text |Cite
|
Sign up to set email alerts
|

Extending Corneal Storage With 2.5% Chondroitin Sulfate (K-Sol)

Abstract: K-Sol ™ corneal storage medium maintains corneal viability for at least ten days, compared with McCareyKauf man (M-K) medium, which does so for a reported maximum of three days. Since many eye banks still use M-K medium exclusively, stored corneas must be used without undue delay, and shipping time further hastens the planned surgery time. Transferring the shipped M-K medium-stored cornea to K-Sol offers a simple way of increasing storage time in our eye bank. Ninety-five out of 100 transferred corneas (95%) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…Similar results were shown by Gregory A Stainer et al (2013) 9 and associates who had done a study at Department of Ophthalmology, University of Wisconsin Hospitals and Clinics, Madison with 130 patients who underwent penetrating keratoplasty with moist chamber and MK media stored donor corneas had found that, MK medium is better alternative when compared to moist chamber if used for preservation within 48 hours after the death of donor.…”
Section: Discussionsupporting
confidence: 78%
“…Similar results were shown by Gregory A Stainer et al (2013) 9 and associates who had done a study at Department of Ophthalmology, University of Wisconsin Hospitals and Clinics, Madison with 130 patients who underwent penetrating keratoplasty with moist chamber and MK media stored donor corneas had found that, MK medium is better alternative when compared to moist chamber if used for preservation within 48 hours after the death of donor.…”
Section: Discussionsupporting
confidence: 78%